2012
DOI: 10.1002/mrm.24437
|View full text |Cite
|
Sign up to set email alerts
|

Spatially selective implementation of the adiabatic T2prep sequence for magnetic resonance angiography of the coronary arteries

Abstract: In coronary magnetic resonance angiography, a magnetization-preparation scheme for T2-weighting (T2Prep) is widely used to enhance contrast between the coronary blood-pool and the myocardium. This pre-pulse is commonly applied without spatial selection to minimize flow sensitivity, but the non-selective implementation results in a reduced magnetization of the in-flowing blood and a related penalty in signal-to-noise-ratio (SNR). It is hypothesized that a spatially-selective T2Prep would leave the magnetization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first fully adiabatic slice‐selective T 2 ‐prep proposed. In a previous work, a twice‐refocused T 2 ‐prep was modified to achieve slice selection using the tip–down and tip–up pulses ; however, the presence of conventional 90° pulses reduces the B 1 robustness of such T 2 ‐prep. Slice‐selective B 1 ‐insensitive pulses (STABLE) derived from BIR4 designs have also been proposed to achieve adiabatic excitation at high field .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first fully adiabatic slice‐selective T 2 ‐prep proposed. In a previous work, a twice‐refocused T 2 ‐prep was modified to achieve slice selection using the tip–down and tip–up pulses ; however, the presence of conventional 90° pulses reduces the B 1 robustness of such T 2 ‐prep. Slice‐selective B 1 ‐insensitive pulses (STABLE) derived from BIR4 designs have also been proposed to achieve adiabatic excitation at high field .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a large value of T2prep could improve image quality. Sahar et al reported that T2 prep technic increased image quality compared to non T2 prep technic (Soleimanifard et al 2013 ). Mueller et al state that dual-source RF transmission with RF shimming results in an optimized SAR distribution, thereby reducing local SAR peaks (Mueller et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future improvements of the T 2 ‐post pulse sequence may include the implementation of a slice‐selective T 2 preparation module. Soleimanifard et al demonstrated that the slice‐selective T 2 ‐prep with a time interval of 150 ms between T 2 ‐prep and the acquisition can improve the SNR and CNR of coronary artery images in diastole. This concept can theoretically also be applied to systolic imaging with the T 2 ‐post technique.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated sequence parameters were the same as for the sequence protocol mentioned below. Tissue parameters were used as follows: arterial blood T 1 /T 2 = 1650/230ms ; myocardium T 1 /T 2 = 1470/43 ms . While a segmented k ‐space gradient echo imaging sequence with multiple RF excitations per cardiac cycle was simulated, the signal from the first RF excitation was used for further analysis.…”
Section: Methodsmentioning
confidence: 99%